Redox Properties of a Rhenium Tetrazolato Complex in Room Temperature Ionic Liquids: Assessing the Applicability of the Stokes-Einstein Equation for a Metal Complex in Ionic Liquids - Silvester, Debbie; Uprety, S.; Wright, P.; Massi, Massimiliano; Stagni, S.; Muzzioli, S. (American Chemical Society, 2012)
The redox properties of a rhenium-tetrazolato complex, namely fac-[Re(CO)3(phen)L] (where L is 5-(4'-cyanophenyl)tetrazolate), have been studied by cyclic voltammetry in a range of common room temperature ionic liquids (RTILs) with different anions and cations. In all eight RTILs, one reduction and two oxidation peaks are observed. It is believed that the reduction peak corresponds to ligand reduction and the two oxidation peaks are two one-electron oxidations of the metal from Re(I) to Re(II) and Re(II) to Re(III). The redox potentials of the metal oxidations appear to be unchanged with the solvent; however, the potential for the reduction peak is more negative in RTILs containing the[P14,6,6,6]+ cation, suggesting a stabilization effect of the electrogenerated intermediate with the other RTIL cations studied (imidazolium and pyrrolidinium). Potential step chronoamperometric experiments were used to calculate diffusion coefficients of the complex in RTILs, and it was found that fac-[Re(CO)3(phen)L] diffuses very slowly through the RTIL medium. A plot of diffusion coefficient against the inverse of viscosity of the RTIL solvent showed a linear trend, suggesting that the Stokes-Einstein relationship generally applies for this complex in RTILs, but the coefficient on the denominator is likely to be closer to 4 (the “slip” limit) than 6 (the “stick” limit) when taking into account the hydrodynamic radius.